Master Legal Vocabulary & Terminology : Legal Vocabulary In Use: Contracts, Prepositions, Phrasal Verbs + 425 Expert Legal Documents & Templates in English! / Marc Roche - Roche, Marc
Master Legal Vocabulary & Terminology: Legal Vocabulary In Use: Contracts, Prepositions, Phrasal Verbs + 425 Downloadable Expert Legal Documents & Templates in English!", provides a structured framework under which law students, lawyers and other law professionals can significantly improve their knowledge of legal vocabulary and terminology. You will be taken through the main vocabulary and grammar structures in commercial contracts and allowed to practise them through highly targeted vocabulary and grammar activities, which aim to develop, not only your lexical and grammatical skills, but also your confidence and overall competence within international legal settings. Towards the end of the book you will find a short glossary with all the main terms of contract law and legal vocabulary in English, together with a phrasal verb mini-dictionary which includes definitions and exercises to perfect your mastery of this area of English. Finally, the last section of this book, contains an amazing selection of 425 legal templates to guide you through drafting contracts, letters, affidavits and many many other documents. It will be an invaluable resource for your studies and career in the legal arena.